The Role of Teachers ’ Instructional Moves on Students ’ Problem-Solving Skills: A Discourse Analysis of Mathematics Lessons in the USA and Tanzania - Kinyota, Mjege (Papers in Education and Development, 2020)
The role of instructional moves in fostering students ' problem-solving skills is well documented. Hence, this study analysed a videotaped interaction of four high school students from one school in the USA solving an ill-structured mathematical problem under teachers ' guidance. Furthermore, five students from one school in Tanzania solved the same problem while their teachers were allowed to observe, after which they were interviewed. Findings indicated that non-judgmental teachers ' instructional moves that requested for students ' explanation, clarification and justification were key to providing scaffolds that helped students during problem solving. Additionally, although Tanzanian teachers perceived several challenges, they had positive opinions regarding ill-structured problems, collaborative problem solving and use of video for reflective practices. Finally, policy and practical implications for mathematics education in Tanzania are discussed. Keywords: collaborative problem solving, ill-structured problems, instructional design, mathematics education,